1994
DOI: 10.1161/01.cir.89.5.2390
|View full text |Cite
|
Sign up to set email alerts
|

Microwave catheter ablation of myocardium in vitro. Assessment of the characteristics of tissue heating and injury.

Abstract: Microwave ablation has the potential to directly heat a greater volume of tissue than RF ablation but only with efficient MW antennas. The primary mechanism of tissue injury for both MW and RF ablation appears to be thermal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 11 publications
2
54
1
1
Order By: Relevance
“…[1][2][3] A precise measurement of the lethal isotherm for radiofrequency ablation is important to clinical practice and the development of new ablation technology. However, the value of the lethal isotherm has not been measured directly.…”
Section: Clinical Perspective On P 378mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] A precise measurement of the lethal isotherm for radiofrequency ablation is important to clinical practice and the development of new ablation technology. However, the value of the lethal isotherm has not been measured directly.…”
Section: Clinical Perspective On P 378mentioning
confidence: 99%
“…[1][2][3] For myocardial tissue, the minimal tissue temperature necessary to produce permanent tissue destruction around the radiofrequency electrode, the lethal isotherm, has only been estimated indirectly. [1][2][3] Using spaced thermocouples and the mathematical relationship of tissue temperature to distance from the radiofrequency electrode, the lethal isotherm for intact myocardium has been estimated to be 47.9°to 53.6°C. 1,3 On the basis of these studies, a tissue temperature of 50°C has been widely…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the success rate in attempts to coagulate the critical parts of the reentrant circuits, 2 approaches can be taken: improving the accuracy of the mapping technique and increasing the size of the lesion created by catheter ablation. Several methods for increasing lesion size have been investigated, ranging from surgery to ablation with direct current, 7,8 laser, 9 microwaves, 10 and alcohol injection 11 to radiofrequency ablation with large-tip [12][13][14][15] or saline-irrigated 16 -19 electrodes. The chosen ablation site may have significant influence on lesion size because of various degrees of cooling of the electrode tip from the intracavitary blood flow, although this has not yet been evaluated systematically.…”
mentioning
confidence: 99%
“…Third, the studies that provide the lethal isotherm estimates of 50°C to 56°C also used the tetrazolium staining method to define acute lesion size. 3,4 These studies found the lethal isotherm to be less than the thermal inactivation temperature of dehydrogenase enzymes (62°C for porcine isoforms), suggesting that thermal enzymatic inactivation is not the limiting factor in determining lesion boundaries. 3,4 The discrepancy between these estimates and our work is likely due to the direct measurement of the temperature at the edge of the lesion in our study and estimation of that temperature by extrapolation in the prior studies.…”
mentioning
confidence: 99%